Palestinian speculative fiction: reimagining home in virtual Palestine - Anis Afifi Norbasudi,; Raihan Rosman, (Penerbit Universiti Kebangsaan Malaysia, 2025)
Palestinian speculative fiction emerges as a powerful and dynamic literary genre, providing a distinctive lens on Palestine’s complex historical, political and cultural landscape. Drawing on Ian Campbell’s assertion that speculative genres inherently reflect postcolonial literature, this paper examines how Palestinian speculative writers utilise this genre to illuminate the complex nostalgia and profound trauma of displaced Palestinians following the pivotal event of the 1945 Nakba. Through the analysis of Saleem Haddad’s “Song of the Birds” (2019), Majd Kayyal’s “N” (2019) and Emad El-Din Aysha’s “Digital Nation” (2019), the paper demonstrates how these authors employ ‘alternate realities’ to depict both the complex longing of the pre-Nakba generation and the resilient resistance adopted by the younger generation in response to the enduring trauma of Israeli occupation. It acknowledges that while there may be no immediate remedy for Palestinian’s longing to return, their narratives persist as powerful expressions of hope and resilience.